The Link Between the SAMFE and Police Perceptions of Victim Credibility. (January 2022) - Yu, Lilly; Walsh, Kelly; Zweig, Janine M.
While research has documented the evidentiary significance of sexual assault medical forensic exams (SAMFEs) to case processing, there has been less focus on SAMFEs' relevance to extralegal case characteristics. This study, through focus groups with police officers and prosecutors, illuminates the link between two important case processing factors: the SAMFE and perceptions of victim credibility. The majority of respondent narratives about the utility of the SAMFE point to how it strengthens or weakens perceptions of victim credibility. This link points to the SAMFE's important role in early case processing before investigators send DNA evidence for forensic testing.